Vitamin D status in relation to physical performance, falls and fractures in the Longitudinal Aging Study Amsterdam: A reanalysis of previous findings using standardized serum 25-hydroxyvitamin D values. Issue 177 (March 2018) - Van Schoor, N.M.; Heymans, M.W.; Lips, P.
Highlights: More people were at risk for low vitamin D status after standardization of serum 25(OH)D values. Associations between serum 25(OH)D and physical functioning, falls and fractures were similar after standardization. Larger differences between original and standardized serum 25(OH)D values were observed in some other cohorts. Standardization is of utmost importance for reaching consensus in clinical cut-offs. Abstract: The Longitudinal Aging Study Amsterdam (LASA) is an ongoing prospective cohort study in a representative sample of Dutch older persons. In previous LASA studies, lower serum 25-hydroxyvitamin D (25(OH)D) values, as assessed by a competitive protein binding assay or radioimmunoassay, have been associated with decreased physical functioning, falls and fractures. Recently, serum 25(OHD) values in LASA were standardized using the Vitamin D Standardization Program (VDSP) protocol as part of the European ODIN project. In the current manuscript, the influence of standardizing serum 25(OH)D values will be discussed using the associations with physical functioning, falls and fractures as examples.